Education and Its Poverty-Reducing Effects: The Case of Paraiba, Brazil - Verner, Dorte (World Bank, Washington, D.C., 2013)
Breaking the intergenerational transmission of poverty requires far-reaching actions in the education sector. Widespread poverty affects both students' performance and their availability to attend school. Low-quality education leads to low income, which in turn perpetuates poverty. Furthermore, low levels of education affect growth though low labor productivity. Although Paraiba, Brazil suffers from a history of educational neglect, the state has recently made significant gains in primary enrollment; 93 percent of the children aged 7-14 are enrolled in school. However, 30 percent of the population aged 15 and older are illiterate and, unfortunately, it is not only the older generations that cannot read and write: 15 percent of children aged 10 to 15 are illiterate. However, substantial achievements in education have helped the extremely poor segment of population as much as expected. Probit analyses reveal that education attainment is the single most important poverty-reducing factor. All levels of education from primary to tertiary are significant and negatively associated with the probability of being poor.